Neutronic model of a stellarator-mirror fusion-fission hybrid - Chernitskiy, S.V.; Moiseenko, V.E.; Noack, K.; Ågren, O.; Abdullayev, A. (Вопросы атомной науки и техники, 2012)
The MCNPX numerical code has been used to model a compact concept for a fusion-fission reactor based on a combined stellarator-mirror trap. Calculation results for the radial leakage of neutrons through the mantle surface of the fission reactor are presented. С помощью программы MCNPX разработана концепция контролированного гибридного реактора не больших размеров на основе открытой ловушки. В работе представлены результаты радиальной утечки нейтронных потоков за пределы моделируемой системы. За допомогою програми MCNPX розроблена концепція контрольованого гібридного реактора не великих розмірів на основі відкритої пастки. В роботі представлено результати розрахунків виходу нейтронних потоків за межі модельованої системи.